Kebijakan Pemanfaatan Ruang pada Sempadan Sungai Kahayan, Kota Palangka Raya - Jesica, Jennie; Cristiana, Edelwisia (Satya Dharma : Jurnal Ilmu Hukum, 2023)
The purpose of this paper was to examine the policies on space utilization control at the Kahayan River border. The author has discussed several provisions related to the Kahayan River area condition which has experienced land conversion, dominated by residential buildings. The type of analysis used was interpretive descriptive. The results of this paper have included regulations regarding the determination of river boundary lines, river management, the utilization of river borders, control of space utilization through zoning regulations, permits, provision of incentives and disincentives, and penalties. Tujuan penulisan untuk menelaah kebijakan terkait pengendalian pemanfaatan ruang pada sempadan Sungai Kahayan. Penulis membahas kondisi faktual terkait kondisi kawasan Sungai Kahayan yang mengalami alih fungsi lahan, didominasi oleh bangunan permukiman. Jenis analisis yang diterapkan adalah deskriptif interpretatif. Hasil dari tulisan ini meliputi peraturan mengenai penetapan garis sempadan sungai, pengelolaan sungai, pemanfaatan sempadan sungai, pengendalian pemanfaatan ruang melalui peraturan zonasi, perizinan, pemberian insentif dan disinsentif, serta sanksi.